Designing of brake timing of autonomous emergency braking system to avoid collision to pedestrians - Keisuke SUZUKI; Hiroaki YAMAGUCHI; Takaharu OGURI (Mechanical Engineering Journal, 2017)
This study analyzes the brake operation behavior of drivers when a pedestrian runs out onto a road with good visibility. For this purpose, 15 subjects were observed in a driving simulator. As the evaluation criteria, we adopted the TTC to avoid the collision to pedestrian in the front/back direction at the start of braking and the spare distance between the pedestrian and the vehicle in the sideways direction at the start of braking. To determine the reliability of these test results, we also analyzed the initiation timing of a driver's braking operation in a real road environment using drive recorders and compared these results with those test results. Then, based on the results of this driving simulator test, we proposed the lowest 1% of the cumulative frequency of the driver's operation timings as the time of starting the brake operation in autonomous emergency braking. Finally, this proposed brake control timing's adequacy was validated in an experiment. The system's brake control did not interfere with the drivers' brake operation, confirming that driver overconfidence in the system was controlled.